Models to identify treatments for the acute and persistent effects of seizure‐inducing chemical threat agents. Issue 1 (28th July 2016) - Pessah, Isaac N.; Rogawski, Michael A.; Tancredi, Daniel J.; Wulff, Heike; Zolkowska, Dorota; Bruun, Donald A.; Hammock, Bruce D.; Lein, Pamela J.
Abstract : Exposures to seizure‐inducing chemical threat agents are a major public health concern. Of particular need is improved treatment to terminate convulsions and to prevent the long‐term neurological sequelae in survivors. We are studying the organophosphorus cholinesterase inhibitor diisopropyl fluorophosphate (DFP) and the GABA receptor inhibitor tetramethylenedisulfotetramine (TETS), which arguably encompass the mechanistic spectrum of seizure‐inducing chemical threats, with the goal of identifying therapeutic approaches with broad‐spectrum efficacy. Research efforts have focused on developing translational models and translational diagnostic approaches, including (1) in vivo models of DFP‐ and TETS‐induced seizures for studying neuropathological mechanisms and identifying treatment approaches; (2) in vivo imaging modalities for noninvasive longitudinal monitoring of neurological damage and response to therapeutic candidates; and (3) higher‐throughput in vitro platforms for rapid screening of compounds to identify potential antiseizure and neuroprotective agents, as well as mechanistically relevant novel drug targets. This review summarizes our progress toward realizing these goals and discusses best practices and mechanistic insights derived from our modeling efforts.